Blue Economy Innovation Impact Assessment with the GMR-Europe Model - Varga, Attila; Hau-Horváth, Orsolya; Szabó, Norbert; Járosi, Péter (Scientific Research, 2013)
This paper introduces and applies a model system that is suitable for the impact assessment of Blue Economy innovations. Our contribution to the literature is threefold. First, we build a multi-sector computable general equilibrium (CGE) model, which provides the theoretical frame for studying the economic impacts of using waste as a production input. Second, we create an empirical methodology through which new technologies of Blue Economy can be concretely accounted for in regional input-output tables. Since Blue Economy innovations are largely built on local inputs, their effects are primarily local. Given that interregional spillovers of local impacts might also be significant, through interregional trade or migration, we applied a modelling approach that is able to follow complex spatial processes. The broader model framework chosen is the GMR-Europe model.
Keywords: GMR Model; Blue Economy; Computable General Equilibrium Models; TFP; Innovation